2017
DOI: 10.1242/jcs.201665
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 mediates the Ca2+ influx required for the interaction between flightless-1 and non-muscle myosin, and collagen remodeling

Abstract: Fibroblasts remodel extracellular matrix collagen, in part, through phagocytosis. This process requires formation of cell extensions, which in turn involves interaction of the actin-binding protein flightless-1 (FliI) with non-muscle myosin IIA (NMMIIA; heavy chain encoded by MYH9) at cell-matrix adhesion sites. As Ca 2+ plays a central role in controlling actomyosin-dependent functions, we examined how Ca 2+ controls the generation of cell extensions and collagen remodeling. Ratio fluorimetry demonstrated loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 55 publications
1
35
0
Order By: Relevance
“…D,E). This observation could be correlated with other results obtained at the cellular level, showing the requirement of active TRPV4 channels for collagen compaction .…”
Section: Discussionsupporting
confidence: 89%
“…D,E). This observation could be correlated with other results obtained at the cellular level, showing the requirement of active TRPV4 channels for collagen compaction .…”
Section: Discussionsupporting
confidence: 89%
“…Studies of the lower urinary tract have indicated that TRPV channels, including TRPV1, TRPV2, TRPV4, TRPM8, and TRPA1, are expressed in the bladder and may act as sensors of stretch and/or chemical irritation (Andersson 2016). Furthermore, it was shown that Ca 2+ influx through TRPV4 channels regulates the interaction between nonmuscle myosin and actin binding protein Flightless I (Arora et al 2017). Taken together, it is plausible that the mechanism underlying DO development in models induced by the use of retinoids as well as the beneficial effects of BLEB in these models is mediated by their effects on TRPV channels.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, substrate stiffness is regulated by the composition of the ECM which changes as a function of physiological (development, aging) and pathophysiological (atherosclerosis, hypertension, fibrosis) processes (90)(91)(92)(93). TRPV4 has been identified as a major mechanosensor for substrate stiffness, but so far this function has been exclusively attributed to parenchymal cells (30,31,(94)(95)(96)). Yet, it is fair to speculate that changes in substrate stiffness will similarly affect the mechanical forces that act upon immune cells during the processes of adhesion and transmigration, which accordingly may affect TRPV4-dependent cellular responses.…”
Section: Trpv4 In Mechanosensation Of Immune Cellsmentioning
confidence: 99%